PERGESERAN MITOS DI TENGAH-TENGAH PERUBAHAN SOSIAL (Mitologi Gua Kiskendo dan Dusun Betetor Kabupaten Kendal) Shifting The Myth In The Middle Of Social Change (The Myth of Kiskendo Cave and Betetor Hamlet in Kendal) - Mulyani Mudis Taruna (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2016)
There are many myths existed in some areas in Indonesia that forbid government officers entering in certain places. This leads to the development of those areas blocked. This research explores and compares between the myth of Kiskendo cave and Betetor village in Kendal district Central Java including how does the origin of those myths, what are the effects of those myths to the surrounding community, and the shifting of its meaning in the society. This study uses phenomenology approach, and data was gathered through in-depth interviews and observation. Analysis was conducted during and after field work using descriptive analysis. Results of this study illustrate that structure of the myth story of Kiskendo cave comes from the story of pewayangan, while the myth of Betetor village is from the story of Kiai Rujak Beling Sabuk Alu who was chased by Dutch army and he enters to Betetor village. The myth of Kiskendo cave does not affect on the government officers’ attitude including police, army, and civil servant. In addition, this myth does not influence to the social change in the village. On the other hand, the myth of Betetor village influence on the government officers’ attitudes, they are afraid to enter the village. However, nowadays they are no longer afraid to enter the village; even some residents become civil servants.